The Role of NHRC in Regulating Health Research Ethics in Nepal: A Narrative Review - Adhikari, Anup; Aryal, Bhagwan; Devkota, Swikriti; Acharya, Hema; K.C., Amita (Journal of Health Promotion, 2023)
This study aims to chart Nepal’s evolution of health research ethics over time and the role of the Nepal Health Research Council (NHRC) in its regulation. This narrative review article mentions the pervasiveness of contract research and the contribution of universities and international organizations in producing data and supporting pilot projects. It further highlights the structural inequalities and limitations of health research in Nepal, including lack of technology, infrastructure, funding, limited access to resources and global scientific networks. It discusses Nepal’s emerging regulatory and ethical field, establishing the NHRC and developing ethical guidelines and review committees. The challenges faced by NHRC in terms of capacity and resources and the need to strengthen research ethics monitoring and compliance are also marked. This article also discusses several key challenges and areas of concern regarding research ethics and capacity building in Nepal’s health research context. The conflicts arising from defining health research and determining which activities require ethical review are highlighted, especially about programmatic interventions and monitoring and evaluation exercises. The need for comprehensive mapping of health research activities is emphasized as an initial step toward understanding the research landscape. Additionally, issues related to timely ethical reviews, the co-investigator’s role, institutional research capacity, data ownership, publication practices, and the ethical considerations of health and development interventions are discussed. It emphasizes redressing these challenges and promoting responsible research practices in Nepal.